Biomass and carbon stock estimation of an Atlantic Forest fragment - Henud, Igor Rodrigues; Manes, Stella; Marinho, Ludmila de Souza Varejão; Clemente, Ana Carolina; Shimabukuro, Júlia Kazue; Tanizaki-Fonseca, Kenny (Revista Agrogeoambiental, 2021)
Carbon sequestration is a crucial ecosystem service, naturally mitigating and reducing the ever-growing threat from climate change. Large forests, such as the Atlantic Forest, are important carbon reservoirs removing carbon from the atmosphere and storing it in their biomass. The assessment of carbon stock from forests fragments helps to establish a better understanding of the carbon cycle and the potential of climate mitigation strategies. Thus, we estimated the biomass and carbon stock of an Atlantic Forest fragment located in the foothills of Pedra de Itaocaia. We used a non-destructive methodology based on climbing techniques and an allometric equation. We climbed seven trees in order to thoroughly measure them in whole and calculate the volume of arboreal compartments. We compared the measured volume obtained from the climb to an estimated tree cylindrical volume and established a correction factor of 0.65 between both (i.e. tree form factor). The tree form factor adjusts the allometric equation and allows carbon estimations without the need to climb all trees in the fragment. The biomass and carbon stock estimates obtained were 100.1 and 50.5 MgC/ha, respectively, which implies that the fragment is on an intermediary stage of regeneration at approximately forty years old. This allometric equation efficiently integrates structural features of forest fragments similar to the one of Pedra de Itaocaia, thus contributing to advance the knowledge about processes taking place in forest fragments situated in the Atlantic Forest. Carbon estimation is imperative for a better understanding of climate mitigation strategies that can revert the threat of climate change to ecosystems.